Determination of plant growth promoting potential of Azotobacter spp. isolated from the rhizosphere of weeds in maize crop (Zea mays L.) - León, Luis H. (2015)
The chemical fertilizer represents for 20 and 30 % of cost the production a crop, used correctly increase productivity and profitability, however, each year increase the among of fertilizer to apply, due to deficiency of soil adsorption and absorption by the plant. Beging maize the third most important crop in Peru, with a significant impact on economic and social activity in 2014, only 40% of the offered maize corresponded of the production nacional. 37 weeds were identified associated with crops of maize from agricultural fields Monsefú districts and Reque, Lambayeque Region, with 68% being dicotyledonous against monocots with 32%. Bacteria were isolated from the rhizosphere of weeds, getting 305 pure cultures of bacteria, 133 of which (43.7%) were identified as Azotobacter spp. Investigated the biochemical reaction in nitrate reduction, utilization of sucrose, glucose, maltose, mannitol, rhamnose, glycerol and sorbitol. Identifying A. vinelandii (58%), A. paspali (13%), A. armeniacus (8%), A. nigricans (8%) and 13 cultives not the species was identified. With this cultives pure of Azotobacter spp. native was quantified to 36.03 ppm of fixed nitrogen as ammonia; 60.75 ppm of indole acetic acid and 6.06 ppm solubilized phosphorus was also determined the activity antagonistic to Fusarium verticillioides, proteolytic and chitinolytic. 20% of Azotobacter spp. native did not affect the emergence of simple hybrid hard yellow corn 144 agriculture, 33% positively affected and 47% negatively affected. In turn, none Azotobacter spp. affect negatively survival. The potential of the plant growth promoter of Azotobacter spp. isolated from weeds in maize crops in the region of Lambayeque been demonstrated.